Inventory of refugia plants potentially medicinal in the agricultural area of Plandaan Subdistrict, Jombang Regency, East Java Province - Anggun Wulandari; Fadhilatus Syarifah (Universitas Lancang Kuning, 2021)
Agricultural and plantation areas dominate the Plandaan subdistrict, so the majority of the livelihoods of its residents are engaged in agriculture. In practice, in addition to using pesticides, crop pest control in the Plandaan subdistrict is to make use of refugia plants. The refugia technique is economical and environmentally friendly because it does not use synthetic chemicals that damage the environment. In addition to acting as natural pest control, refugia plants are also known to have potential as medicines. This study aimed to inventory or collect medicinal plants refugia in the agricultural area of ​​the Plandaan subdistrict. This study used descriptive explorative methods. Data collection techniques were carried out through observation and directly documenting species of refugia plants with potential drugs found in the area of observation plots. In this study, the subject was a potentially medicinal refugia plant found on an observational plot with a plot size of 10 × 10 meters. The observations were three plots of agriculture fields and three plots of telajakan (open space). The frequency of refugia plants found from the study on the plot of agriculture fields as many as 1035 plants, while in the plot of telajakan as many as 1007 plants consisting of 37 types of species that each has different medicinal potentials, such as heat and fever lowering, treating cough, flu, skin diseases, and wounds. Agriculture field plots had more frequency of potentially medicinal refugia plants than telajakan plots.